COVID‐19 and the boundaries of open science and innovation: Lessons of traceability from genomic data sharing and biosecurity. (21st October 2020) - Minari, Jusaku; Yoshizawa, Go; Shinomiya, Nariyoshi
Abstract : The COVID‐19 crisis has further highlighted the challenges for open science and data sharing in biomedical research and the need for more traceability and transparency.